2013
DOI: 10.1152/ajprenal.00261.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic urethral activity in response to pharmacological activation of 5-HT1A receptors in the rat

Abstract: In this study, we examined the possibility that 5-HT 1A receptors may underlie sexually dimorphic mechanisms affecting the regulation of urethral functions in anesthetized rats. Simultaneous recordings of intravesical pressure under isovolumetric conditions, external urethral sphincter-electromyography, and urethral perfusion pressure were used to examine the effects of a 5-HT1A receptor agonist [8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT)] and antagonist (WAY-100635) on bladder and urethral functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…Although the urethra is more complex because it is not a rigid pipe and has the property of elasticity, the urethral cross-sectional diameter or area remains a critical factor determining the UFR. A study indicated that 8-OH-DPAT significantly reduced the urethral pressure during the micturition reflex in female rats treated with an NMB agent (14); this finding implies that 8-OH-DPAT may facilitate the urethral smooth muscle relaxation and increase the urethral cross-sectional diameter, thereby raising the UFR. This hypothesis was supported by our finding that the maximal UFR markedly increased at the initial segment of the entire flow duration (ϳ30% of the flow duration).…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mgmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the urethra is more complex because it is not a rigid pipe and has the property of elasticity, the urethral cross-sectional diameter or area remains a critical factor determining the UFR. A study indicated that 8-OH-DPAT significantly reduced the urethral pressure during the micturition reflex in female rats treated with an NMB agent (14); this finding implies that 8-OH-DPAT may facilitate the urethral smooth muscle relaxation and increase the urethral cross-sectional diameter, thereby raising the UFR. This hypothesis was supported by our finding that the maximal UFR markedly increased at the initial segment of the entire flow duration (ϳ30% of the flow duration).…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mgmentioning
confidence: 97%
“…A study indicated that 8-OH-DPAT exerts a significant excitatory effect on pudendal-to-pudendal reflexes; this triggers the EUS burst center in the spinal cord, generating a prolonged EUS burst activity during voiding (4,14). However, the prolonged zero level of oscillatory waves did not continue after the 8-OH-DPAT treatment in rats with a paralyzed EUS (compare Fig.…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mgmentioning
confidence: 98%
See 3 more Smart Citations